A Performance Art como propedêutica da experiência : construção de sentidos e significados sobre, com e por meio do corpo - Terra Nova, Jessica Vitorino da Silva (2016)
In order to point out the "Performance Art" as propaedeutics of experience in the context of the discipline "Philosophy, Education and Body," mandatory curricular component of the Licentiate's Degree in Physical Education from the Federal University of Sergipe (Universidde Federal de Sergipe) and their contributions to the construction of meanings and significances, with and through the body, in its multiple experiences, this paper intends to point out pedagogical possibilities of "propaedeutics" – meaning structural preparation of the ways of experience - from the perspective of Performance Art. The proposition of this manifestation as methodological possibility is presented as a demonstration that enables, through experience, to rescue some senses both for education in general, and for physical education. The structuralist mode of thought from this perspective is subdued from the proposition that the propaedeutics - suspended here from Performance Art - can be interpreted as a possible way to structure and determine the experience of the subject in front of an object to be known under the pedagogical practices at school. The work shows a research of nature "ethnographic" imprint "participant", which was developed together with students enrolled in the course "Philosophy, Education and Body" of the Licentiate's Degree in Physical Education from the Federal University of Sergipe. The propaedeutics structure provided the concreteness of experience whose intention was based on the prospect of imbuing a change in a behavior among (future) professionals, transformation and instrumentation of the students to propose new meaning practices of the content area to make possible the perception of the body in its complexity, as a symbolic front field to a culture in order to transcend the dualistic and Cartesian view which has influenced this field of knowledge.